The cell polarity proteins Boi1 and Boi2 direct an actin nucleation complex to sites of exocytosis in Saccharomyces cerevisiae - Glomb, Oliver; Wu, Yehui; Rieger, Lucia; Rüthnick, Diana (Journal of cell science, 2020)
Owing to the local enrichment of factors that influence its dynamics and organization, the actin cytoskeleton displays different shapes and functions within the same cell. In yeast cells, post-Golgi vesicles ride on long actin cables to the bud tip. The proteins Boi1 and Boi2 (Boi1/2) participate in tethering and docking these vesicles to the plasma membrane. Here, we show in Saccharomyces cerevisiae that Boi1/2 also recruit nucleation and elongation factors to form actin filaments at sites of exocytosis. Disrupting the connection between Boi1/2 and the nucleation factor Bud6 impairs filament formation, reduces the directed movement of the vesicles to the tip and shortens the vesicles' tethering time at the cortex. Transplanting Boil from the bud tip to the peroxisomal membrane partially redirects the actin cytoskeleton and the vesicular flow towards the peroxisome, and creates an alternative, rudimentary vesicle-docking zone. We conclude that Boi1/2, through interactions with Bud6 and Bni1, induce the formation of a cortical actin structure that receives and aligns incoming vesicles before fusion with the membrane.